Public Speaking as Performance Subtitle Practicing Public Speaking in the Theatre & Performance Classroom - Leon, Mechele (Open textbook library.)
Public Speaking as Performance: Practicing Public Speaking in the Theatre & Performance Classroom is an innovative public speaking textbook written by theatre educators. It combines the essential elements of speechwriting with the tried and true skills that actors learn to communicate a story to an audience. In chapters such as “Actor Tools for Public Speakers” and “From Page to Stage,” the textbook provides students with a creative and accessible approach to delivering speeches. Drawing on the tradition of teaching public speaking in theatre and drama departments—a practice that is still maintained in some institutions—this textbook emphasizes the performative nature of communication. Educators teaching public speaking in theatre and performance departments will find this a textbook particularly suited to the interests of their students.